2021
DOI: 10.2174/1874364102115010156
|View full text |Cite
|
Sign up to set email alerts
|

Computer Vision Syndrome Prevalence and Ocular Sequelae among Medical Students: A University-Wide Study on a Marginalized Visual Security Issue

Abstract: Introduction: This study aimed to discover and document the potential of visual and ocular sequelae of computer vision syndrome (CVS) among medical students. Methods: This cross-sectional case-control study was conducted on medical students (n=4030) of five universities in Egypt. All students completed a specially designed and validated CVS questionnaire survey (CVS-F3). Students with ≥5 CVS symptoms constituted a ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…In India, 82.3% of students experienced one or more symptoms of digital vision syndrome during the intensive lockdown of COVID-19 (38). Also, accommodative asthenopia has been reported in medical students from Egypt, 84.8 to 87.9% of students had complaints included in the CVS (26,39). In another study, 95 % of medical students reported having at least one symptom of CVS during their study time (40).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In India, 82.3% of students experienced one or more symptoms of digital vision syndrome during the intensive lockdown of COVID-19 (38). Also, accommodative asthenopia has been reported in medical students from Egypt, 84.8 to 87.9% of students had complaints included in the CVS (26,39). In another study, 95 % of medical students reported having at least one symptom of CVS during their study time (40).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, our bivariate analysis did not show differences in terms of screen time in individuals with and without CVS. Even so, there are reports that state a direct relationship between screen time and the development of CVS (26). Tawil et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,11,12,16 The available evidence suggests that as little as two hours of sustained digital device usage a day is likely to develop a range of vision-related problems. 4,17,18 Reddy et al, Mohan, et al and Iqbal et al estimated that CVS affected between 50% and 90% of students taking virtual classes in the Middle East. 5,18,19 CVS is categorized into four strains: asthenopic CVS (manifests as eye strain, eye dryness, soreness, headache, and fatigue), ocular surface CVS (dryness, grittiness, irritation, redness, burning sensation, and heaviness often due to environmental factors, blinking rates, and use of lenses/ glasses), visual CVS (double or blurred vision, presbyopia, and slow focus change), and extraocular CVS (musculoskeletal pain).…”
Section: Computer Vision Syndromementioning
confidence: 99%
“…In addition to the use of more than one device, older age, employment status, sedentary lifestyles, usage of re-wetting drops, gender, and optical correction. 8,17,22,[34][35][36] It's notable, however, that self-reported awareness/complaints may be misleading in the absence of clinical assessments, particularly given leading responses in the questionnaire. Iqbal et al's study of 4030 medical students drawn from five universities in Egypt, for example, found that while self-reported awareness of CVS was 84.8%, ophthalmic assessments of the same respondents showed only 56% prevalence.…”
Section: Nature Accuracy and Completeness Of Information About Cvsmentioning
confidence: 99%